Developing teacher competencies through the open and distance learning approach in Zimbabwe - Mswazi, J.; Blignaut, S. (South African Journal of Higher Education, 2019)
The main purpose of the study was to gain insights into the effectiveness of the open and distance learning approach (ODLA) as an empowering tool in upgrading rural teachers’ professionalism. The data to address the problem was collected by means of a case study methodology. The results of the study indicate that female teachers involved in the study perceive the ODLA to be enabling in several respects. Firstly, the ODLA provided rural teachers with the flexibility and opportunities to switch careers midway. Secondly, the ODLA provided female teachers with new professional knowledge, skills and competences with minimal disruptions to their family, social and work commitments. Thirdly, the ODLA was regarded as cost effective in terms of access, affordability, effort and time management. In light of the above, this study calls for further comparative studies of ODLA to other teacher education models in improving teacher proficiencies in resource-stressed environments.